2020
DOI: 10.1101/2020.09.30.321182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth-dependent signals drive an increase in early G1 cyclin concentration to link cell cycle entry with cell growth

Abstract: Entry into the cell cycle occurs only when sufficient growth has occurred. In budding yeast, the cyclin Cln3 initiates cell cycle entry in late G1 phase by inactivating Whi5, a repressor that blocks transcription of genes that drive cell cycle entry. Growth-dependent changes in the concentrations of Cln3 and/or Whi5 have been proposed to link cell cycle entry to cell growth. However, there are conflicting reports regarding the behavior and roles of Cln3 and Whi5 during G1 phase, and little is known about th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 64 publications
(120 reference statements)
3
9
1
Order By: Relevance
“…Lucena et al shows an elutriation experiment with normally sized cells where the ratio of Whi5 and Cln3 protein amounts decreases as cells grow through G1 phase after release from poor into rich media (see Supplemental Figure S4 for quantitation of this experiment from Lucena et al, 2018). The latter was confirmed recently by Sommer et al, who conclude that "Whi5 concentration decreased by ∼30% in rich carbon and 20% in poor carbon, consistent with the fact that Whi5 protein levels do not change substantially" [in G1] (Sommer et al, 2021). We note that the ambiguous term "levels" in Sommer et al refers to protein amounts.…”
Section: Introductionsupporting
confidence: 81%
“…Lucena et al shows an elutriation experiment with normally sized cells where the ratio of Whi5 and Cln3 protein amounts decreases as cells grow through G1 phase after release from poor into rich media (see Supplemental Figure S4 for quantitation of this experiment from Lucena et al, 2018). The latter was confirmed recently by Sommer et al, who conclude that "Whi5 concentration decreased by ∼30% in rich carbon and 20% in poor carbon, consistent with the fact that Whi5 protein levels do not change substantially" [in G1] (Sommer et al, 2021). We note that the ambiguous term "levels" in Sommer et al refers to protein amounts.…”
Section: Introductionsupporting
confidence: 81%
“…Plotting the Cln3 concentration over the full time course reveals a clear pulse of Cln3 (Figure 6E). This Cln3 pulse is consistent with earlier elutriation-Western blot experiments (Thorburn et al, 2013;Zapata et al, 2014), with recent new experiments (Sommer et al, 2021), and with our published findings (Litsios et al, 2019).…”
Section: Cln3 Oscillations Have Been Documented In the Recent Literaturesupporting
confidence: 92%
“…Our previous studies (Dorsey et al, 2018;Litsios et al, 2019;Black et al, 2020) and the additional experiments reported here provide a coherent body of evidence that Whi5 is not diluted by measurable amounts during G1 phase, hence making less likely the hypothesis that Start is primarily triggered by Whi5 dilution. Results inconsistent with the Whi5 dilution model of Start control during G1 phase have also been reported elsewhere (Blank et al, 2018;Garmendia-Torres et al, 2018;Barber et al, 2020;Sommer et al, 2021). In addition to evidence from our groups, other previous work also suggests that Start is controlled primarily by the increase in the protein synthesis rate in G1 phase and the concomitant synthesis of the unstable Start activator Cln3 (Thorburn et al, 2013;Zapata et al, 2014;Sommer et al, 2021).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…G 1 cyclins are highly unstable ( 49 , 50 ), and this property allows cells to rapidly down-regulate their levels after transcriptional shut-off and, hence, quickly prevent entry into the cell cycle as a response to unfavorable conditions. In budding yeast, whereas G 1 cyclins are unstable throughout the cell cycle ( 51 ), the overall levels of Cln3 display a slight but significant increase during G 1 under nonperturbed conditions ( 52 ). Despite the relevance of degradation in cyclin regulation, its modulation during G 1 progression and cell cycle entry has not been analyzed.…”
Section: Discussionmentioning
confidence: 99%